Research and Technology Institutes (RTIs) in a latecomer innovation system: evidence from the Information and Communications Technology (ICT) industry in Brazil. (23rd January 2006) - Figueiredo, Paulo N.; Vedovello, Conceicao; Melo, Marne; Marins, Luciana M.
This article seeks to add new empirical evidence, from a late-industrialising standpoint, to the literature related to the way in which Research and Technology Institutes (RTIs) contribute to building up a National System of Innovation (NSI). This study is based on a sample of 11 RTIs in Brazil that are dedicated to the Information and Communications Technology (ICT) industry. The framework for capabilities identifies three dimensions: technical, organisational and human resources. Links between RTIs and other organisations of the innovation system (e.g., universities, technical centres, laboratories and firms) are examined here as key sources to build up such capabilities. Over the past few years, the capabilities of the sampled RTIs have not been confined to basic levels. Several RTIs have progressively upgraded their capabilities to carry out innovative activities. This contributes to building up an NSI in Brazil. Links between RTIs and other innovation system organisations vary from informal, human resource based and formal (e.g., joint research). Our findings contradict some current arguments that point to a pervasive deterioration of innovation systems in countries like Brazil, following the policy changes from the 1990s and the intensification of globalisation.